Facilitating entrepreneurial discovery in smart specialisation via stakeholder participation within online mechanisms for knowledge-based policy advice - Katharina Fellnhofer (Cogent Business & Management, 2017)
The European Commission expends much effort toward the facilitation of smart specialisation strategies for smart, sustainable, and inclusive economic growth in Europe. In this framework, stakeholder engagement has received growing attention but is often neglected by the academic community, possibly due to the complexity of a multi-stakeholder approach in knowledge-based policy advice. In this regard, platforms with online mechanisms particularly show promising potential to engage a diverse set of stakeholders, so-called quadruple helix stakeholders, throughout the development of smart specialisation strategies. This report discusses a conceptional approach for promoting stakeholder engagement using online mechanisms for knowledge-based policy advice. This paper recommends seven propositions for future empirical testing of hypotheses to provide a robust fundament for future research. Because of this scope of policy advice via stakeholders, this contribution is particularly relevant for policy-makers, researchers, entrepreneurs, and the society at large interested in cultivating a knowledge-based economy via online mechanisms for exchanging policy advice.
Keywords: 650